Increasing Mentalization to Reduce Maladaptive Defense in Patients With Mental Disorders - Hayden, Markus C.; Müllauer, Pia K.; Beyer, Klea J. P.; Gaugeler, Richard; Senft, Birgit; Dehoust, Maria C.; Andreas, Sylke (Frontiers in Psychiatry, 2021)
Background: There are indications of associations between the ability to mentalize and psychological defense mechanisms. However, only a few studies have focused on these associations, and even fewer have included empirical analyses. In the present study, we aimed to fill this research gap by analyzing the link between the ability to mentalize and psychological defense mechanisms in patients with mental disorders. We examined whether changes in defense mechanisms are predicted by an increase in mentalization or whether such changes are only related to reductions in psychopathology and interpersonal problems. Methods: A clinical sample of N=89 patients was studied during and after inpatient psychiatric rehabilitation. Repeated-measures analyses of variance were performed to determine changes in mentalization, psychological defense, psychopathology, and interpersonal problems over the course of therapy and posttreatment. Linear regression analyses were used to predict the change in defense patterns based on an increase in mentalization. Results: Maladaptive defense mechanisms were significantly reduced during inpatient therapy and remained low until follow-up, whereas neurotic and adaptive defense mechanisms did not change significantly. The results of the regression analyses indicated that mentalization played an important role in the reduction in maladaptive defense during and after inpatient rehabilitation for mental disorders, whereas reductions in psychopathology and interpersonal distress were only partially associated with a reduction in maladaptive defense. Conclusion: We conclude that mentalization is vital for reducing maladaptive defense mechanisms, which are commonly associated with mental disorders. In therapy, an increase in patients’ capacity to mentalize may be a practicable approach to diminish maladaptive defense mechanisms.